Substitutability, Complementarity and the Theory of Derived Demand - Sato, R.; Koizumi, T. (Review of Economic Studies, 1970)
Ryuzo Sato, Tetsunori Koizumi; Substitutability, Complementarity and the Theory of Derived Demand1, The Review of Economic Studies, Volume 37, Issue 1, 1 Januar